A modified sulfide electrolyte and applications thereof
Patent Information
- Application Number
- CN202111329324.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-10
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2041-11-10
AI Technical Summary
然而,通常需要加入引发剂以引发单体聚合并得到聚合物电解质,外加的引发剂往往会与电池内其他组分发生副反应,从而对电池性能造成不利影响
[0017](1)本发明提供的改性硫化物电解质,利用硫化物电解质本身的特点以引发单体聚合生成聚合物电解质,避免了使用对储能器件性能不利的引发剂,同时将硫化物固态电解质与聚合物电解质结合,该电解质既具有较高的离子电导率,又具有较佳的柔韧性,适用于制成电解质薄膜。
Smart Images

Figure CN116111181B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sulfide electrolyte technology, and more specifically, relates to a modified sulfide electrolyte and its application. Background Technology
[0002] The application of energy storage technology in distributed power grids can improve energy utilization, reduce environmental pollution, and enhance the thermal economy and safety stability of the system. Lithium-ion batteries, as an important energy storage method, are widely used in production and daily life. However, lithium-ion batteries using organic liquid electrolytes have potential safety issues, such as electrolyte flammability and leakage. Using solid-state electrolytes can effectively improve battery safety and energy density. Solid-state electrolytes can be classified into sulfide electrolytes, oxide electrolytes, and polymer electrolytes. Among them, sulfide electrolytes have high ionic conductivity and a certain degree of plasticity, which is beneficial for increasing the electrode / electrolyte contact area. Therefore, sulfide electrolytes are considered one of the most promising solid-state electrolytes.
[0003] However, existing sulfide electrolytes still suffer from drawbacks such as brittleness, poor flexibility, and susceptibility to cracking under stress, making them unsuitable for high-capacity pouch cells and hindering the realization of their high energy density advantages. Introducing polymer electrolytes, which possess good flexibility and film-forming properties, into sulfide electrolytes can effectively compensate for these shortcomings. However, initiators are typically required to initiate monomer polymerization and obtain the polymer electrolyte. These added initiators often undergo side reactions with other components within the battery, adversely affecting battery performance. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a modified sulfide electrolyte and its application, which can be prepared only by using a sulfide solid electrolyte, a monomer that can undergo polymerization reaction and an electrolyte salt, without the need to add an initiator. The resulting modified sulfide electrolyte has the dual advantages of both sulfide electrolytes and polymer electrolytes.
[0005] To achieve the above objectives, the present invention provides a modified sulfide electrolyte, which is formed by initiating monomer solution polymerization using a sulfide solid electrolyte as an initiator. The monomer solution includes liquid monomers that can undergo polymerization reactions initiated by the sulfide solid electrolyte and electrolyte salts dissolved in the monomers.
[0006] Preferably, the liquid monomer is one or more of cyclic lactones, acrylates and acrylate oligomers that still contain double bonds on one side, and cyanoacrylates.
[0007] Preferably, the sulfide solid electrolyte is in a glassy, glass-ceramic, or crystalline state.
[0008] Preferably, the sulfide solid electrolyte is one or more of the following types: thio-LISICON, LGPS, thio-germanium ore, and NASICON.
[0009] Preferably, the concentration of electrolyte salt in the monomer solution is less than or equal to 3 mol / L.
[0010] Preferably, the preparation method of the modified sulfide electrolyte includes the following steps: pressing the sulfide solid electrolyte into a sheet, then dropping a monomer solution onto the surface of the sheet-like sulfide solid electrolyte, letting it stand at room temperature for a period of time, and waiting for the monomer solution to polymerize on the surface of the sheet-like sulfide solid electrolyte to form a polymer electrolyte film, thereby obtaining the modified sulfide electrolyte;
[0011] The modified sulfide electrolyte is used in all-solid-state energy storage devices with alkali metal as the negative electrode. The polymer electrolyte film can prevent side reactions between the sulfide solid electrolyte and the alkali metal negative electrode, thereby improving the stability of the sulfide solid electrolyte and the alkali metal negative electrode.
[0012] Preferably, the preparation method of the modified sulfide electrolyte includes the following steps: mixing a monomer solution with a sulfide solid electrolyte in a certain proportion and grinding to obtain a slurry; placing the obtained slurry on a substrate and letting it stand at room temperature for a period of time, whereby the sulfide solid electrolyte initiates the polymerization of liquid monomers to generate a polymer electrolyte, while simultaneously forming an electrolyte membrane on the substrate; applying pressure to thin the obtained electrolyte membrane, and then peeling the electrolyte membrane off the substrate to obtain the modified sulfide electrolyte membrane.
[0013] More preferably, the obtained slurry is scraped or spin-coated onto the substrate, left to stand at room temperature for a period of time, and then rolled to thin it out.
[0014] More preferably, the mass ratio of the sulfide solid electrolyte to the monomer solution is 1:(0.04-24).
[0015] According to another aspect of the present invention, an all-solid-state energy storage device is also provided, which includes the modified sulfide electrolyte described above.
[0016] In summary, the technical solutions conceived by this invention have the following beneficial effects compared with the prior art:
[0017] (1) The modified sulfide electrolyte provided by the present invention utilizes the characteristics of the sulfide electrolyte itself to initiate monomer polymerization to generate polymer electrolyte, avoiding the use of initiators that are detrimental to the performance of energy storage devices. At the same time, the sulfide solid electrolyte is combined with the polymer electrolyte, which has both high ionic conductivity and good flexibility, making it suitable for making electrolyte films.
[0018] (2) In this invention, a monomer solution is dropped onto the surface of a sulfide electrolyte sheet. The sulfide electrolyte can initiate the polymerization of the monomer solution and form a thin polymer electrolyte layer on its surface. The resulting modified sulfide electrolyte, used as the electrolyte in a solid-state alkali metal battery, can separate the sulfide electrolyte from the alkali metal anode, thereby suppressing side reactions between the sulfide electrolyte and the alkali metal. Compared with the traditional element doping method to improve the stability of the sulfide solid-state electrolyte and the alkali metal, this method is simple, efficient, and low-cost, avoiding the cumbersome steps and energy consumption of high-speed ball milling and high-temperature sintering.
[0019] (3) In this invention, a sulfide solid electrolyte is mixed and ground with a monomer solution. The sulfide electrolyte particles initiate in-situ polymerization of the monomer solution, resulting in a tight bond between the polymer electrolyte and the sulfide electrolyte. The polymer electrolyte acts as a binder, significantly improving the mechanical strength of the sulfide electrolyte sheet and reducing the thickness of the sulfide electrolyte membrane. Compared with traditional sulfide electrolyte membrane preparation methods, this method effectively avoids the use of binders and solvents, simplifies the preparation process of the sulfide electrolyte membrane, and is suitable for preparing sulfide electrolyte membranes of different shapes.
[0020] (4) The modified sulfide electrolyte provided by the present invention is used in all-solid-state energy storage devices. Due to the high ionic conductivity and good flexibility of the modified sulfide electrolyte, the interface contact between the electrolyte and the electrode of the all-solid-state energy storage device is good, and it has excellent electrochemical stability. It is especially suitable as an electrolyte for high-energy-density soft-pack batteries. Attached Figure Description
[0021] Figure 1 Li in Embodiment 1 of the present invention 5.5 PS 4.5 Cl 1.5 Electrolyte sheets and prepared PCL-Li 5.5 PS 4.5 Cl 1.5 XRD pattern of electrolyte tablets.
[0022] Figure 2 Li in Embodiment 1 of the present invention 5.5 PS 4.5 Cl 1.5 Surface morphology (a) and cross-sectional morphology (b) of the electrolyte sheet.
[0023] Figure 3 The PCL-Li prepared in Example 1 of this invention 5.5 PS 4.5 Cl 1.5 Surface morphology (a) and cross-sectional morphology (b) of the electrolyte sheet.
[0024] Figure 4 Li in Embodiment 1 of the present invention 5.5 PS 4.5 Cl 1.5 Electrolyte sheets and prepared PCL-Li 5.5 PS 4.5 Cl 1.5 Lithium-ion conductivity diagram of the electrolyte sheet.
[0025] Figure 5 The PCL-Li prepared in Example 1 of this invention 5.5 PS 4.5 Cl 1.5 Electrolyte sheet (a) and Li 5.5 PS 4.5 Cl 1.5 The impedance diagram corresponding to the lithium-ion conductivity diagram of electrolyte sheet (b).
[0026] Figure 6 The above are the nuclear magnetic resonance (NMR) H-s spectra of the polymer electrolyte membrane and the monomers used in the polymer in Example 1 of this invention.
[0027] Figure 7 The graph shows the cycle performance of the Li / Li battery prepared in Comparative Example 1 of this invention at different current densities.
[0028] Figure 8 The Li / Li battery prepared in Comparative Example 1 of this invention was tested at 0.1 mA cm⁻¹. -2 Cyclic performance at current density.
[0029] Figure 9 The graph shows the cycle performance of the Li / Li battery prepared in Example 7 of this invention at different current densities.
[0030] Figure 10 The Li / Li battery prepared in Example 7 of this invention is at 0.1 mA / cm. -2 Cyclic performance at current density.
[0031] Figure 11 The images show the XRD patterns of the modified sulfide electrolyte membranes prepared in Examples 9 to 12 of this invention.
[0032] Figure 12 The graph shows the lithium-ion conductivity of the modified sulfide electrolyte membranes prepared in Examples 9 to 12 of this invention.
[0033] Figure 13 This is a surface morphology diagram of the modified sulfide electrolyte membrane prepared in Example 12 of the present invention. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0035] A modified sulfide electrolyte is formed by initiating monomer solution polymerization using a sulfide solid electrolyte as an initiator. The monomer solution includes liquid monomers that can undergo polymerization reactions initiated by the sulfide solid electrolyte and electrolyte salts dissolved in the monomers.
[0036] The modified sulfide electrolyte of this invention contains a sulfide solid electrolyte and a polymer electrolyte. The polymer electrolyte is formed by monomer solution polymerization initiated by the sulfide solid electrolyte, without the need for additional initiators. This effectively avoids side reactions between the added initiator and other components in the battery. The resulting modified sulfide electrolyte has the dual advantages of both sulfide solid electrolytes and polymer electrolytes, exhibiting both good ion conductivity and good flexibility and plasticity.
[0037] The liquid monomers described in this invention include, but are not limited to, one or more of cyclic lactones, acrylates and acrylate oligomers that still contain double bonds on one side, and cyanoacrylates, preferably one or more of lactide, caprolactone, or polyethylene glycol dimethacrylate. The sulfide solid electrolyte includes, but is not limited to, glassy, glass-ceramic, or crystalline states, wherein crystalline sulfide solid electrolytes include, but are not limited to, one or more of thio-LISICON, LGPS, Argyrodite, and NASICON types. More preferably, the sulfide solid electrolyte is Li... 5.5 PS 4.5 Cl 1.5 Na 3.75 [Sn 0.67 Si 0.33 ] 0.75 P 0.25 S4 or Na 3.57 [Sn 0.67 Si 0.33 ] 0.67 P 0.33 S 3.9 X 0.1 X is Cl, Br, or I. The electrolyte salt is a lithium salt, sodium salt, or potassium salt.
[0038] Preferably, the lithium salt is lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalateborate)borate (LiBOB), lithium difluorooxalateborate (LiDFOB), and lithium trifluoromethanesulfonate (LiCF3SO3).
[0039] The sodium salts are sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium bis(fluoromethanesulfonyl)imide (NaFSI), sodium bis(oxalateborate)borate (NaBOB), sodium di(fluorooxalateborate)borate (NaDFOB), and sodium trifluoromethanesulfonate (NaCF3SO3).
[0040] The potassium salts are potassium hexafluorophosphate (KPF6), potassium hexafluoroarsenate (KAsF6), potassium perchlorate (KClO4), potassium tetrafluoroborate (KBF4), potassium bis(trifluoromethanesulfonyl)imide (KTFSI), potassium bis(trifluoromethanesulfonyl)imide (KFSI), and potassium trifluoromethanesulfonate (KCF3SO3).
[0041] In some embodiments, the concentration of electrolyte salt in the monomer solution is less than or equal to 3 mol / L.
[0042] Typically, high-energy-density solid-state energy storage devices require alkali metals as anodes. However, sulfide electrolytes and alkali metals are prone to side reactions, leading to instability in both the sulfide electrolyte and the alkali metal anode, thus affecting the performance of the energy storage device. This severely hinders the application of sulfide electrolytes in all-solid-state energy storage devices. Currently, common methods to improve the stability of sulfide electrolytes and alkali metals include preparing alloy-type anodes and elemental doping, but these methods involve complex processes and high costs.
[0043] To overcome the shortcomings of the prior art, the present invention provides a method for preparing a modified sulfide electrolyte, comprising the following steps: pressing a sulfide solid electrolyte into a sheet, then dropping a monomer solution onto the surface of the sheet-like sulfide solid electrolyte, allowing it to stand at room temperature for a period of time, until the monomer solution polymerizes on the surface of the sheet-like sulfide solid electrolyte to form a polymer electrolyte film, thereby obtaining the modified sulfide electrolyte.
[0044] This modified sulfide electrolyte is used in all-solid-state energy storage devices with alkali metal as the negative electrode. Because a polymer electrolyte film is formed on the surface of the sulfide electrolyte sheet, the sulfide electrolyte and alkali metal can be effectively separated, suppressing side reactions between the sulfide electrolyte and alkali metal, thereby improving the stability of the sulfide electrolyte and alkali metal.
[0045] In some embodiments, the settling time at room temperature is 1 hour to 3 hours.
[0046] Currently, the solid electrolyte sheets used in sulfide-based all-solid-state batteries are typically fabricated using cold pressing or hot pressing techniques with battery molds. However, these methods produce sulfide electrolyte sheets that are small in area, thick, brittle, and lack flexibility, making them unsuitable for high-capacity pouch cells, thus hindering the realization of the battery's high energy density advantage. Therefore, the preparation of sulfide solid electrolyte membranes with good ion conductivity and mechanical properties is crucial and urgent.
[0047] The present invention provides a method for preparing a modified sulfide electrolyte membrane, comprising the following steps:
[0048] S1. Mix the monomer solution with the sulfide solid electrolyte in a certain proportion and grind them to obtain a slurry;
[0049] S2. Place the slurry obtained in step S1 on the substrate and let it stand at room temperature for a period of time. The sulfide solid electrolyte initiates the polymerization of liquid monomers to generate polymer electrolyte, and at the same time, an electrolyte film is formed on the substrate.
[0050] S3. The electrolyte membrane obtained in step S2 is subjected to pressure to thin it, and then the electrolyte membrane is peeled off from the substrate to obtain the modified sulfide electrolyte membrane.
[0051] The modified sulfide electrolyte membrane prepared by this invention features a tightly integrated sulfide solid electrolyte and polymer electrolyte, forming a continuous ion transport channel. The sulfide solid electrolyte serves as the main component of the ion transport channel, while the polymer electrolyte acts as a binder, significantly improving the mechanical strength of the modified sulfide electrolyte membrane. Compared to existing sulfide electrolyte membrane preparation methods, this method utilizes the characteristic that sulfide electrolytes can initiate the polymerization of liquid monomers, effectively avoiding the use of binders and solvents, simplifying the preparation process. Furthermore, this method can prepare sulfide electrolyte membranes of various shapes, showing broad application prospects in all-solid-state energy storage devices.
[0052] Specifically, in steps S2 and S3, the obtained slurry can be scraped or spin-coated onto a substrate and left to stand at room temperature for 1 to 3 hours to form an electrolyte membrane on the substrate; then, the obtained electrolyte membrane is thinned by roller pressing to obtain a modified sulfide electrolyte membrane. For the scraping method, the membrane thickness is controlled by changing the thickness of the scraper.
[0053] For spin coating, in order to achieve better spin coating results, it is advisable to dilute the slurry with a non-polar or low-polar solvent. The non-polar or low-polar solvents include, but are not limited to, ethyl acetate, fluorobenzene, trifluorobenzene, chlorobenzene, o-dichlorotoluene, toluene, xylene, phenol, dichloromethane, chloroform, 1,2-dichloroethane, and chloroform. The concentration of the diluted slurry is about 0.05 g / L to 0.2 g / L. The diluted slurry is then dropped onto the substrate, and the spin coating speed is adjusted to 500 rpm / s and the time is 30 s. The concentration and volume of the slurry are kept constant, and the number of spin coatings is changed to control the film thickness.
[0054] For the roll forming thinning process, the roll forming temperature is 25℃~100℃.
[0055] Alternatively, the obtained slurry can be directly placed between two substrates and allowed to stand at room temperature for 1 to 3 hours to form an electrolyte membrane between the two substrates. Then, it can be hot-pressed or cold-pressed using a hot press for a certain period of time to obtain a sulfide electrolyte membrane. When using hot pressing, the hot pressing temperature is 40℃ to 100℃, and the hot pressing time is 0.5 to 24 hours. When using cold pressing, the cold pressing temperature can be at room temperature, and the cold pressing time is 0.5 to 24 hours.
[0056] In some embodiments, the substrate used in this invention is preferably a polytetrafluoroethylene (PTFE) membrane.
[0057] In some embodiments, the mass ratio of the sulfide solid electrolyte to the monomer solution is 1:(0.04-24), preferably 1:(0.04-0.9), and more preferably 4:1.
[0058] In some embodiments, the thickness of the modified sulfide electrolyte membrane is 5 μm to 500 μm.
[0059] The present invention provides an all-solid-state energy storage device, which can be an all-solid-state chemical battery or an all-solid-state supercapacitor, and includes the modified sulfide electrolyte provided by the present invention.
[0060] The modified sulfide electrolyte provided by this invention serves as the electrolyte for all-solid-state energy storage devices. Since the modified sulfide electrolyte combines the advantages of both sulfide electrolytes and polymer electrolytes, the electrolyte and electrode interface of this all-solid-state energy storage device has good contact, resulting in good rate performance and cycle stability.
[0061] This invention provides a method for preparing a solid-state alkali metal battery, which includes the following steps: first, a sulfide solid electrolyte is packed into a mold battery and pressed into a sheet; then, a positive electrode is laid on one side and compacted; a monomer solution is dropped onto the other side; after standing at room temperature for a period of time, the monomer solution polymerizes to form a polymer film; then, an alkali metal negative electrode is assembled on this side to obtain a solid-state battery.
[0062] This invention provides a method for preparing a solid-state alkali metal battery, which includes the following steps: assembling the modified sulfide electrolyte membrane prepared in this invention between the positive electrode and the alkali metal negative electrode to obtain a solid-state battery.
[0063] In some embodiments, the alkali metal negative electrode is lithium metal, sodium metal, or potassium metal.
[0064] In some embodiments, the active material of the positive electrode is lithium iron phosphate, lithium cobalt oxide, ternary nickel cobalt manganese, sulfur positive electrode, sulfurized polyacrylonitrile, sodium iron phosphate, sodium vanadium phosphate, or potassium manganese ferricyanide (such as K2Mn[Fe(CN)6]).
[0065] The above technical solution will be described in detail below with reference to specific embodiments.
[0066] Example 1
[0067] The sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5 The electrolyte sheet was pressed into a thickness of approximately 80 μm; LiTFSI was dissolved in caprolactone to prepare a solution containing 1 mol L... -1 A solution of caprolactone from LiTFSI was then added dropwise to the surface of the electrolyte tablet, and allowed to stand for 2 hours to obtain a modified sulfide electrolyte tablet.
[0068] The sulfide solid electrolyte and the modified sulfide electrolyte (denoted as PCL-Li) 5.5 PS 4.5 Cl 1.5 Perform XRD testing, such as Figure 1 As shown, the polymerization of caprolactone on the surface of the sulfide electrolyte sheet has no effect on the structure of the sulfide.
[0069] The two electrolytes were characterized by SEM, such as Figure 2 and Figure 3 As shown, caprolactone can form a polymer film layer of about 10 μm on the surface of the sulfide electrolyte, and this polymer layer is mainly formed on the surface of the sulfide electrolyte sheet.
[0070] The conductivity of the two electrolytes was tested, such as... Figure 4 and Figure 5 As shown, Li 5.5 PS 4.5 Cl 1.5 The lithium-ion conductivity is 5.6 × 10⁻⁶. -3 S cm -1 PCL-Li 5.5 PS 4.5 Cl 1.5 The room temperature lithium-ion conductivity is 10. -4Scm -1 .
[0071] The modified sulfide electrolyte tablets were dissolved in deuterated chloroform. The resulting solution was filtered through a polytetrafluoroethylene (PTFE) membrane to obtain a clear solution. This solution was subjected to NMR spectroscopy (H2N), and the caprolactone monomer was also subjected to NMR spectroscopy (H2N) (using deuterated chloroform as the solvent). Figure 6 As shown, caprolactone polymerizes to form polycaprolactone, indicating that Li 5.5 PS 4.5 Cl 1.5 It can initiate the polymerization of caprolactone.
[0072] Example 2
[0073] Same as Example 1, except that the monomer solution contains 3 mol L -1 LiFSI caprolactone solution.
[0074] Example 3
[0075] Similar to Example 1, except that the solvent in the monomer solution is a mixture of caprolactone monomer and lactide monomer, with a mass ratio of caprolactone to lactide of 9:1.
[0076] Example 3
[0077] Similar to Example 4, except that the mass ratio of caprolactone to lactide is 8:2.
[0078] Example 5
[0079] Same as Example 1, except that the monomer solution contains 1 mol L -1 LiTFSI polyethylene glycol dimethacrylate solution.
[0080] Example 6
[0081] Similar to Example 1, except that the sulfide electrolyte used is Na. 3.75 [Sn 0.67 Si 0.33 ] 0.75 P 0.25 S4, the monomeric solution contains 1 mol L -1 NaTFSI caprolactone solution.
[0082] Comparative Example 1
[0083] The Li used in the same embodiment 1 5.5 PS 4.5 Cl 1.5 Lithium sheets were stacked on both sides of the electrolyte sheet to assemble a symmetrical battery, and its cycle performance was tested at different current densities, such as... Figure 7 As shown, Li5.5 PS 4.5 Cl 1.5 The critical current density for metallic lithium is 0.3 mA cm⁻¹. -2 .
[0084] For the assembled Li / Li battery at 0.1 mA cm -2 Cyclic performance was tested at current density, such as... Figure 8 As shown, when the current density is 0.1 mA cm⁻¹ -2 During the cycle, the polarization potential continuously increases, indicating that Li 5.5 PS 4.5 Cl 1.5 It has poor stability with lithium metal and constantly undergoes side reactions.
[0085] Example 7
[0086] PCL-Li prepared in Example 1 5.5 PS 4.5 Cl 1.5 Lithium sheets were stacked on both sides of the electrolyte sheet to assemble a symmetrical battery, and its cycle performance was tested at different current densities, such as... Figure 9 As shown, PCL-Li 5.5 PS 4.5 Cl 1.5 The critical current density for metallic lithium is 2 mA cm⁻¹. -2 .
[0087] For the assembled Li / Li battery at 0.1 mA cm -2 Cyclic performance was tested at current density, such as... Figure 10 As shown, when the current density is 0.1 mA cm⁻¹ -2 At that time, the polarization potential remained almost unchanged during the cycling process, indicating that PCL-Li 5.5 PS 4.5 Cl 1.5 It exhibits good stability with lithium metal. A comparison with Comparative Example 1 shows that this modified sulfide electrolyte can significantly improve the stability of Li... 5.5 PS 4.5 Cl 1.5 Stability with lithium metal.
[0088] Example 8
[0089] Similar to Example 7, except that in PCL-Li 5.5 PS 4.5 Cl 1.5 A lithium metal anode was added to one side of the electrolyte sheet, and a lithium iron phosphate positive electrode active material was added to the other side. The battery was then assembled and tested.
[0090] Example 9
[0091] LiTFSI was dissolved in caprolactone to prepare a solution containing 1 mol L -1 LiTFSI caprolactone solution. The sulfide solid electrolyte Li... 5.5 PS 4.5 Cl 1.5 The slurry was prepared by mixing the caprolactone solution at a mass ratio of 50:50 and grinding. Ethyl acetate was added to the slurry, mixed thoroughly, and the concentration of the diluted slurry was adjusted to 0.1 g / L. The diluted slurry was then spin-coated onto a PTFE substrate at a speed of 500 rpm / s for 30 seconds, and allowed to stand at room temperature for 2 hours. 5.5 PS 4.5 Cl 1.5 Liquid caprolactone polymerization is initiated, and a modified sulfide solid electrolyte membrane is formed on the substrate. The resulting electrolyte membrane is then thinned by roll pressing at a temperature of 60°C. Finally, the electrolyte membrane is peeled off from the PTFE membrane substrate to obtain a thin modified sulfide electrolyte membrane.
[0092] Example 10
[0093] Similar to Example 9, except that the sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5 The mass ratio of the monomer solution to the monomer solution is 60:40.
[0094] Example 11
[0095] Similar to Example 9, except that the sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5 The mass ratio of the monomer solution to the monomer solution is 70:30.
[0096] Example 12
[0097] Similar to Example 9, except that the sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5 The mass ratio of the monomer solution to the monomer solution is 80:20.
[0098] The modified sulfide electrolyte membranes obtained in Examples 9-12 were subjected to XRD tests, such as... Figure 11 As shown, the XRD pattern of the composite electrolyte membrane exhibits peaks for both polymer electrolyte and sulfide electrolyte, indicating successful preparation of the composite electrolyte membrane and that the obtained polymer has no effect on the sulfide electrolyte. The modified sulfide electrolyte membranes obtained in Examples 9-12 were subjected to lithium-ion conductivity testing, as shown... Figure 12As shown, the composite electrolyte membranes prepared in Examples 10-12 all exhibited an ionic conductivity of approximately 10. -4 S cm -1 The composite electrolyte membrane prepared in Example 9 exhibits low ionic conductivity at lower temperatures, but its ionic conductivity can reach 10 Ω·cm at higher temperatures. -4 S cm -1 This may be because the monomer concentration in the slurry is high, and the monomers are not completely polymerized. As the temperature increases, the unpolymerized monomers further polymerize. The morphology of the electrolyte membrane obtained in Example 12 was characterized from... Figure 13 It can be seen that the sulfide electrolyte particles are linked together by the polymer electrolyte to form an organic-inorganic composite electrolyte membrane.
[0099] As can be seen from the above embodiments, the modified sulfide electrolyte prepared by this invention avoids the use of initiators that are detrimental to battery performance. The preparation method is simple, rapid, and low-cost, and has broad application prospects. This invention uses liquid monomers to form a polymer electrolyte film in situ on the surface of the sulfide electrolyte sheet. This method can improve the stability of different types of sulfide electrolytes with alkali metals. Furthermore, due to the fluidity of the liquid, the compatibility of the solid-solid interface in all-solid batteries can be effectively improved. In the modified sulfide electrolyte film prepared by this invention, the sulfide solid electrolyte and the polymer electrolyte form a continuous alkali metal ion transport channel. The sulfide solid electrolyte acts as the main body of the ion transport channel, while the polymer electrolyte acts as a binder, which can significantly improve the mechanical strength of the modified sulfide electrolyte film and reduce its thickness.
[0100] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A modified sulfide electrolyte, characterized in that: The monomer solution is formed by initiating monomer solution polymerization using a sulfide solid electrolyte as an initiator. The monomer solution includes liquid monomers that can undergo polymerization reactions initiated by the sulfide solid electrolyte and electrolyte salts dissolved in the monomers. The liquid monomer is one or more of lactide, caprolactone, or polyethylene glycol dimethacrylate; the sulfide solid electrolyte is Li 5.5 PS 4.5 Cl 1.5 Na 3.75 [Sn 0.67 Si 0.33 ] 0.75 P 0.25 S4 or Na 3.57 [Sn 0.67 Si 0.33 ] 0.67 P 0.33 S 3.9 X 0.1 X is Cl, Br or I; the mass ratio of the sulfide solid electrolyte to the monomer solution is 1:(0.04~0.9); The preparation method of the modified sulfide electrolyte includes the following steps: pressing the sulfide solid electrolyte into a sheet, then dropping a monomer solution onto the surface of the sheet-like sulfide solid electrolyte, letting it stand at room temperature for a period of time, and waiting for the monomer solution to polymerize on the surface of the sheet-like sulfide solid electrolyte to form a polymer electrolyte film, thereby obtaining the modified sulfide electrolyte.
2. The modified sulfide electrolyte according to claim 1, characterized in that: The concentration of electrolyte salt in the monomer solution is less than or equal to 3 mol / L.
3. The modified sulfide electrolyte according to claim 1 or 2, characterized in that, The preparation method of the modified sulfide electrolyte includes the following steps: mixing a monomer solution with a sulfide solid electrolyte in a certain proportion and grinding to obtain a slurry; placing the obtained slurry on a substrate and letting it stand at room temperature for a period of time, during which the sulfide solid electrolyte initiates the polymerization of liquid monomers to generate a polymer electrolyte, while simultaneously forming an electrolyte membrane on the substrate; applying pressure to thin the obtained electrolyte membrane, and then peeling the electrolyte membrane off the substrate to obtain the modified sulfide electrolyte membrane.
4. The modified sulfide electrolyte according to claim 3, characterized in that: The obtained slurry is scraped or spin-coated onto the substrate and left to stand at room temperature for a period of time until an electrolyte film forms on the substrate. Then, it is rolled to thin it.
5. An all-solid-state energy storage device, characterized in that: Includes the modified sulfide electrolyte according to any one of claims 1-4.
Citation Information
Patent Citations
Organic-inorganic composite electrolyte with three-dimensional bicontinuous conductive phase and preparation method thereof, and application of organic-inorganic composite electrolyte with a three-dimensional bicontinuous conductive phase
CN110112460A